2015
DOI: 10.1039/c4ta06763k
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-based synthesis of a zeolite imidazolate framework ZIF-100 membrane with high H2/CO2 selectivity

Abstract: A highly permselective ZIF-100 molecular sieve membrane has been prepared on a polydopamine (PDA)-modified support. Attributed to the formation of strong covalent and non-covalent bonds between PDA and ZIF-100, the ZIF-100 nutrients are attracted and bound to the support surface, thus promoting the growth of well-intergrown and phase-pure ZIF-100 membranes. The developed ZIF-100 membranes show high H 2 /CO 2 selectivity due to the outstanding CO 2 adsorption capacity of ZIF-100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 64 publications
(83 reference statements)
3
82
0
Order By: Relevance
“…Caro et al have reported on the use of several ZIF-material supported membranes made of ZIF-95, 39 functionalized ZIF-90, 40 ZIF-7 (ref. 19) and ZIF-100 (ref. 41) for H 2 /CO 2 separation at working temperatures up to 325 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Caro et al have reported on the use of several ZIF-material supported membranes made of ZIF-95, 39 functionalized ZIF-90, 40 ZIF-7 (ref. 19) and ZIF-100 (ref. 41) for H 2 /CO 2 separation at working temperatures up to 325 °C.…”
Section: Introductionmentioning
confidence: 99%
“…22,34,39 As can be seen in Fig. S6, CNT@IL/ZIF-9 hybrid membrane obtained in this work can maintain the gas permeability and selectivity over 500 hours, showing superiority compared to the reported MOF membranes.…”
mentioning
confidence: 68%
“…S8. 34 In conclusion, a novel zeolitic imidazolate framework (ZIF-9) hybrid membrane was grown on the porous α-Al 2 O 3 support covered with CNTs functionalized by ILs using heat treatment of 90 layer-by-layer deposition method. The hybrid membrane CNT@IL/ZIF-9 showed excellent gas separation performance for H 2 /CO 2 because of the cooperative effect of ZIFs, CNTs and ILs.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Properties like high selectivity for H 2 , significant durability, mechanical and hydrothermal stability in reducing environments, as well as operating temperature ranges above 500 °C, make dense ceramic mixed proton-electronic conductors a promising alternative to precious metals and related alloys (Ag-Pd)12, polymers13, metal-organic frameworks (MOFs)1415, zeolite16 or other ceramic microporous materials1718.…”
mentioning
confidence: 99%